1930
DOI: 10.3382/ps.0090296
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium-Phosphorus Ratio in the Nutrition of Growing Chicks

Abstract: Published with the permission of the Director of the Wisconsin Agricultural Experiment Station.The Ca-P ratio in cows milk as well as the milk of other mammals is approximately 1 :.65. It has been found by Simmonds 1 that the optimum amounts of calcium and phosphorus for the rat are approximately .65 gram of calcium and .40 gram of phosphorus per 100 grams of food mixture. These proportions give a Ca-P ratio of 1 :.62, a ratio quite similar to that found in milk. Because of the ideal character of milk as a foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

1932
1932
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 1 publication
2
6
0
Order By: Relevance
“…The day-old chicks contained approximately 0.14 grams calcium and 0.11 grams phosphorus. These values are in harmony with those obtained by Hart, Scott, Kline and Halpin (1930), for the contents of eggs incubated for 20 days and with the calcium contents of day-old chicks as found by Mitchell, Card and Hamilton (1931). There is also good general agreement with the results of Ackerson,Blish & Mussehl (193S) for day-old chicks.…”
supporting
confidence: 82%
“…The day-old chicks contained approximately 0.14 grams calcium and 0.11 grams phosphorus. These values are in harmony with those obtained by Hart, Scott, Kline and Halpin (1930), for the contents of eggs incubated for 20 days and with the calcium contents of day-old chicks as found by Mitchell, Card and Hamilton (1931). There is also good general agreement with the results of Ackerson,Blish & Mussehl (193S) for day-old chicks.…”
supporting
confidence: 82%
“…Experiment 6.-The next experiment was conducted along similar lines for the purpose of studying the effect of adding various amounts of rice bran to the original diet after its calcium-phosphorus ratio had been changed from 1.54:1 to 3.24:1 by substituting calcium carbonate for the bone meal. * The results indicated that 6 * Recent experimental work [Bethke, Kennard, Kick, and Zinzalian (1929) and Hart, Scott, Kline, and Halpin (1930)] has indicated that the optimum calcium-phosphorus ratio of the chick is between 2:1 and 4:1. Wilgus (1931), claims that it is between 1:1 and 2:2:1 and that "A ratio of 2 :S :1 is borderline while 3:3:1 is disastrous."…”
Section: Methodsmentioning
confidence: 91%
“…Massengale (1929) reported that a rachitogenic diet low in Ca and high in P produced a noticeable leg weakness at an earlier age than a diet low in P and high in Ca. Hart, Scott, Kline, and Halpin (1930) observed that with a minimum amount of vitamin D the best calcification and growth was obtained at a Ca/P ratio of 4:1 to 3.3:1 with 2.49 percent to 2.71 percent Ca and 0.66 percent to 0.83 percent P in the ration. Wilgus (1931) advanced evidence to show that when an optimum supply of the antirachitic factor is provided, the Ca/P ratio * Published with the permission of the Director of the Wisconsin Agricultural Experiment Station.…”
mentioning
confidence: 95%